Occupational Perceptions of Physical Education and Sports Students: A Qualitative Study - Uzun, Meliha (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2020)
Teachers embracing their occupations, proud of being a member of teaching profession and valuing work ethics can be considered as having the qualities required by this profession. Their perceptions about teaching affects what they think about their roles in the society, to what degree they are motivated and how they conduct teaching [3]. This study was directed towards examining occupational perceptions of physical education and sports students. To this aim, opinions of 12 physical education and sports students at Sirnak University about their occupations were obtained. The study has a phenomenological design and criterion sampling was used. Data were collected through metaphors. The students were asked to fill in an interview form to determine their occupational perceptions and draw a picture to reveal their opinions reflecting their occupational perceptions. Obtained data were transferred to Nvivo and analyzed with content analysis. Based on the results of the analysis, occupational perceptions of the students were categorized into nine themes: i.e. success, without barriers, effects, universality, development, discovery, leadership, socialization and providing guidance. Teaching was found to be an important factor in guiding individuals' lives, creating a lifestyle, personal, physical, mental and social development, acquiring new skills in accordance with available interests and abilities, and raising generations beneficial to the society. In addition, individuals with special needs were thought to have talents in different fields and sports activities were found to be effective in discovering these talents and helping them to become a member of the society. It was concluded that teaching was an important occupation for the students in terms of family, environment, society and the generation raised.
Keywords: Physical Education; Sports; Teacher; Occupational Perception